Bank guarantees in international trade : the law and practice of independent (first demand) guarantees and standby letters of credit in civil law and common law jurisdictions /: the law and practice of independent (first demand) guarantees and standby letters of credit in civil law and common law jurisdictions. ([2013]) - Bertrams, R. I. V. F (Roeland I. V. F.)
No abstract available